2000
DOI: 10.1111/1467-8624.00152
|View full text |Cite
|
Sign up to set email alerts
|

Development of Face Processing: The Effect of Face Inversion

Abstract: The present experiment examined the degree to which analytic and holistic modes of processing play a role in the way children and adults categorize upright and inverted faces. Seven-year-old children (n = 38), 10-year-old children (n = 40), and adults (n = 55) were instructed to classify upright and inverted faces into two categories. The construction of the categories allowed participants to categorize the faces either analytically (by focusing on a single attribute) or holistically (in terms of overall simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 33 publications
9
106
3
Order By: Relevance
“…These findings stand in contrast to several reports suggesting that adult-like configural face processing does not occur until early to late childhood (for example, Diamond 1977, 1994;Schwarzer 2000;Brace et al 2001). Furthermore, the results are consistent with the model of perceptual narrowing (Nelson 2001(Nelson , 2003 in face processing.…”
Section: Discussioncontrasting
confidence: 89%
“…These findings stand in contrast to several reports suggesting that adult-like configural face processing does not occur until early to late childhood (for example, Diamond 1977, 1994;Schwarzer 2000;Brace et al 2001). Furthermore, the results are consistent with the model of perceptual narrowing (Nelson 2001(Nelson , 2003 in face processing.…”
Section: Discussioncontrasting
confidence: 89%
“…The late maturation hypothesis posits that children do not remember faces as accurately as adults because face processing ability does not fully develop until at least adolescence (see Carey & Diamond, 1977;Mondloch, Le Grand, & Maurer, 2002). Evidence from the basic face processing literature suggests that children's sensitivity may be poorer because they tend to engage in more feature-based rather than configural-based processing (Mondloch, Geldart, Maurer, & Le Grand, 2003: Mondloch, et al, 2002Schwarzer, 2000). The recognition of faces using configural information may not reach adult levels until adolescence (Bruce et al, 2000;Carey, Diamond, & Woods, 1980;Mondloch, et al, 2003: Mondloch, et al, 2002.…”
Section: Receiver Operating Characteristic Analysis Of Age-related Chmentioning
confidence: 99%
“…§ Therefore, one needs a developmental perspective on the acquisition of normal face recognition, as configural perception of faces develops gradually during childhood (13,14,(49)(50)(51)(52). For example, Carey and Diamond (14) have shown that 6-year-old children were equally fast on recognizing inverted and upright faces, whereas 10-year-old children were somewhat delayed on inverted faces but still less so than adults, suggesting that they rely more on configural properties than younger children [see also Mondloch et al (51)].…”
Section: Figmentioning
confidence: 99%